Morphometric Appraisal of Human Atlas and Axis Vertebrae with Its Clinical Implications - Xalxo, Neha; Mehta, Vandana; Patel, Ajay Kumar (Morphometric Appraisal of Human Atlas and Axis Vertebrae with Its Clinical Implications, 2025)
The Atlas and Axis vertebrae are an integral part of a highly specialised anatomical region called as cranio-vertebral junction, which is responsible for critical neurovascular protection and dynamic head and neck movement. This study was conducted on 50 dry human Atlas and 50 Axis vertebrae from an Indian population at the Department of Anatomy, Vardhman Mahavir Medical College and Safdarjung Hospital, New Delhi. The aim of the study was to evaluate the morphometric details, to compare the right and left-sided morphometric values and to explore any morphological variations of the Atlas and Axis vertebrae. The statistical analysis was also carried out. Mean A-P diameter of Atlas vertebrae was 41.88. The distance from the lateral most edge of the FT to the tip of TP of the right was 9.19 mm and 8.28 mm on the left side, respectively. The significant difference of 0.049 was observed between the two sides C1 vertebrae. In one specimen, a hook-shaped bony projection was observed emanating from the superior aspect of TP. This bony projection tapered gradually and was directed antero-medially. The mean height of the dens was 13.95 mm. The mean length of the SAF of C2 on the right side was found to be 16.80 mm and 16.85 mm on the left side. No significant statistical difference was found between the two sides. The mean width of the right SAF was 16.12 mm and 15.2 mm on the left side. A statistically significant difference of 0.042 was observed in the mean width of the SAF on the two sides C2 vertebrae. The study underscores the need for population-specific anatomical data to enhance surgical planning and reduce the risk of injury to vital neurovascular structures.